Mathematical modeling of the main technological parameters of the two-rotor shock-centrifugal disintegrator on the basis of correlation analysis - Nadutyi Volodymyr; Loginova Anastasiia; Sukhariev Vitalii (E3S Web of Conferences, 2019)
Technological disintegration indicators (productivity and power consumption) were determined and their generalized multiple regression variability depending on the regime and structural parameters of the shock-centrifugal disintegrator and the parameters of the output product were obtained. Economic and technological advantages of using the two-rotation kinematic scheme of a shock-centrifugal disintegrator, which implements the destruction of the material mainly by shock shifts due to the combined action of the kinetic energy of the interconnected flows, were justified. The research was carried out using such types of rocks: granite, tuff, limestone, basalt. The nature of the dependencies was determined by comparing the corresponding values of the reliability of different types of approximation.